IGLESIA Y PODER POLÍTICO: UN FRAGMENTO DE HISTORIA COMUNAL (PALMARES, 1866-1920). - Pérez Yglesias, María (1993)
The objective of this paper is to illustrate with a fragment of Palmares canton history (1866-1920) the relationship among ecclesiastic institution, State and local power. Is in this period that community belonging sense is built and he residents identify themselves as "palmarians". Some historical processes of this canton are presented due to the fact that they show the priest leadership, and the controversy and conflict with political power of communities.